Meta-Analysis Of the Effect of Learning Style on Student Learning Outcomes - Rania Atara Isra; Fatni Mufid (KONSTAN - JURNAL FISIKA DAN PENDIDIKAN FISIKA, 2022)
This study presents the results of research on the results of the influence of learning styles on learning outcomes. The research method used in this study is a meta-analysis method. The research method is quantitative. In this study, the sample used is ten relevant articles. For data collection using observation techniques, namely data collection techniques carried out through direct observation of articles. The results of the study on the influence of learning styles on learning outcomes obtained show the effect size value is 0.755, which means that there is an influence of learning styles on student learning outcomes. For the influence of learning styles based on learning materials, static fluid material has a high effect size and based on education level, at the high school level has a large influence between learning styles and student learning outcomes.